Gender Differences in Respiratory Morbidity and Mortality of Preterm Neonates - Townsel, Courtney Denise; Emmer, Sawyer F.; Campbell, Winston A.; Hussain, Naveed (Frontiers in Pediatrics, 2017)
For the past century, researchers have underscored the “disadvantage” observed in respiratory morbidity and mortality of male newborns. In this contemporary review, we examine gender differences in preterm infant respiratory morbidity and mortality specifically appraising differences in the very low birth weight (VLBW) population as well as the late preterm (LPT) population. In the era of postnatal surfactant and antenatal corticosteroids, the gender gap in neonatal outcomes has not narrowed. Structural, physiologic, and hormonal sex differences may be at the root of this disparity. Further exploration into the origin of gender differences in respiratory morbidity and neonatal mortality will shape future therapies. These therapies may need to be gender specific to close the gender gap.